Generation of sarconoids from angiosarcoma patients as a systematic-based rational approach to treatment - Da Jung Jung; Jae Hee Byeon; Young Chul Kim; Woo Shik Jeong; Jong-Woo Choi; Gi Seok Jeong (Journal of Hematology & Oncology, 2024)
Abstract Angiosarcoma is a rare subtype of malignant neoplasm originating from vascular or lymphatic endothelial cells; its low incidence has posed significant challenges for comprehensive investigations into its pathogenic mechanisms and the development of innovative treatment modalities through in vitro and in vivo models. Recent endeavors spearheaded by patient-partnered research initiatives have aimed to elucidate the intricacies of angiosarcomas by leveraging biological omics approaches, with the overarching objective of enhancing prognostic indicators and therapeutic options for this uncommon pathology. To bridge the gap between preclinical research and translational applications, we engineered angiosarcoma-derived organoids from surgically resected primary tumors, hereafter referred to as “sarconoids,” as a proof-of-concept model. A novel protocol for the establishment of these sarconoids has been developed and validated. To ensure that the sarconoids faithfully recapitulate the heterogeneity and complexities of the patients’ original tumors, including transcriptomic signatures, cell-type specificity, and morphological traits, exhaustive histological and transcriptomic analyses were conducted. Subsequently, we expanded the scope of our study to include an evaluation of a sarconoid-based drug screening platform; for this purpose, a drug library (AOD IX), supplied by the National Cancer Institute’s Developmental Therapeutics Program, was screened using 96-well plates. Our findings suggest that sarconoids can be reliably generated from angiosarcoma patient-derived tissues and can serve as accurate models for evaluating therapeutic responses, thereby holding far-reaching implications for translational research and clinical applications aimed at advancing our understanding and treatment of angiosarcoma.